Karakterisasi Fenotip dan Kekerabatan Varietas Jagung Lokal Kabupaten Timor Tengah Utara - Polikarpia Wilhelmina Bani (Savana Cendana, 2018)
Phenotype characters of plant is very important for plant breeding. The aim of this study is characterization phenotype and genetic relationship of local maize in North Central Timor Regency. Local maize varieties that used ini this study namely ‘pena molo’, ‘pena fatu’, ‘pena kikis’, and ‘pena boto’. Phenotype characters to be observed comprise fourteen phenotype characters to evaluate genetic variation. Measuring of phenotype characters based on qualitative and quantitative characteristic. The data of phenotype character obtained analyzed using Multi Variate Statistical Package (MVSP) with UPGMA (Unweighted Pair-Group Method with Arithmetic Average) and Gower General Macthing Coefficient to dendogram constructive. Result of thi study showing similarity coefficient based on phenotype characters is 0,43% to 1 %.